The characterisation of coated bolt and nut for oil and gas industry - Nurul Izzati, Ahmad (2016)
Corrosion is a common problem encountered in the oil and gas industry. Oil and gas pipelines, refineries and petrochemical plants have serious corrosion problems. Internal corrosion in oil and gas industry is generally caused by water, carbon dioxide (CO2) and hydrogen sulfide (H2S), and also can be aggravated by microbiological activity. In this research the investigation of the effectiveness of different layer of zinc spray coat in different salinity to protect the metal are investigated. The sample are sprayed into different layers of zinc spray and immerse into different concentration of Sodium Chloride (NaCl). The test done toward the sample are adhesion test by knife, adhesion test by tape and hardness test by pencil . The study shown that the 5 layer of zinc coated sample are the most effective compared to the other 4 different layers. In this research, the comparision between fluorocarbon coated and zinc coated also were investigated. the final result show that fluorocarbon coated sample is better to protect the pipeline in the oil and gas industry compared to the zinc coated sample due the better performance of fluorocarbon coated sample.